PSO BASED HARMOIC MITIGATION IN SINGLE PHASE SINE WAVE VOLTAGE SOURCE INVERTER - Singh N.M, Spencer Prathap; T, Ajitha (International Journal of Research -GRANTHAALAYAH, 2023)
This paper explains the pruning of power harmonics in a single-phase voltage source inverter using PI controller by calculating the optimized values of PI constants by Particle Swarm Optimization (PSO) Algorithm. The mapping state space model of the sine wave inverter was formulated by considering the operating sequence of full bridge sine wave inverter. The controller acts effectively thereby reducing the voltage and current THDs in an inverter. The PSO technique is implemented which estimates the optimized parameters of constant for PI controller thereby tuning the controller for reducing the total harmonics of a full bridge inverter. The MATLAB / SIMULINK tool and experimental verifications are done for harmonic reduction, and it is found that its harmonics were reduced well than IEEE standards with improved transient response.